Wood gasification for heat and power the Philippine experience - Cruz, Ibarra E.
The technology of wood gasification for heat and power in the Philippines is discussed, starting with research and development activities in 1968 in several institutions in the country (notably the University of the Philippines), the commercialization efforts to propagate wood charcoal gasifiers by the Gasifier and Equipment Manufacturing Corporation (GEMCOR) in 1981, the monitoring of performance of several gasifier-engine systems in actual field operation, a study commissioned by the World Bank in 1983, culminating with a survey of 64 gasifier installations and interviews with 29 gasifier owners in 1985 to determine the problems and hindrances to widespread use of gasifiers in the country. A number of gas producer systems are described and operational data presented. Experiences in marketing of the systems are recounted and reasons for the failure to propagate wide use of the technology are evaluated.